Law and morality at war - Haque, Adil Ahmad (Oxford : Oxford University Press, 2017)
What are the moral and legal issues of contemporary warfare? Drawing on cutting-edge debates in moral philosophy, this work proposes how the laws of war can be evaluated, criticized, and reformed, making a valuable and timely contribution to a pressing international debate.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 14, 2017).
Keywords: War (International law); Law -- Moral and ethical aspects; Law; International law